The Vocabulary Mastery Of The Second Year Students In SMK Sudirman Wonogiri 2001/2002 - Maryadi, Maryadi (2012)
The specific aims of this study are to describe the vocabulary mastery the students after doing the test and to describe the strength and weakness of the second year students of SMK Sudirman Wonogiri in Wonogiri. The study is classroom action research which is conducted in two cycles and it is conducted through the step of learning, planning, acting, observing, and implementing. The study is conducted on February 2001 in SMK Sudirman Wonogiri. The method of collecting data is test, observation, and interview. The data are analyzed by quantitative and qualitative. The implementation of the vocabulary mastery of the second year students in smk sudirman wonogiri 2001/2002 consist of the result pre-test and post test. The materials given the teacher are from the handbook. To know the result of the second year students vocabulary mastery, the writer gives two kinds of test, namely: post test and post test. In the pre test, the highest score is 100, the lowest score test is 20, and the mean score is 58,07. In the post test, the highest score is 90, and the lowest score test is 40, and the mean score is 74,2. The writer concludes that the students achieve the target of vocabulary mastery well. The strength are: the students have a high interest and motivation in teaching learning process, and they are helped understanding pronouncing, and spelling the words. The weaknesses are : the teacher must spend his time and money to get the materials, and need more energy to demonstrate the materials.